Review on the utilization of waste material as a potential substitute for the phase change material used in thermal energy storage system - Siti Amirah, Abdul Ghani; Sumaiya, Zainal Abidin; Saidatul Shima, Jamari (2018)
Recently, great attention has been focused on the application of thermal energy storage (TES) as one of the key solution towards the most effective heat and energy storage system. TES in a form of phase change material (PCM) has been recognized as one of the efficient method for energy management and conservation system. PCM has been widely used in many applications and significant number of literatures has been published to highlight the potential use of PCM as TES material. In the last few decades, various combination of materials has been used to improve the quality and performance of PCM. However, although the information is quantitatively enormous and the application of waste has becoming a trending subject nowadays, documented researches on PCM material derived from waste material are still very scarce. Therefore, in this paper, in-depth reviews on the implementation of potential waste materials in PCM considering its purposes in improving the TES performance, economic values and environment were explored, investigated and reviewed. Overall, this review shows a potential utilization of waste materials as a new substitute to produce an efficient, cost-effective and environmentally friendly PCM in the future TES system.